Adherence to Islamic principles of success and academic achievement - Zuwaira Abubakar; Isa Muhammad Maishanu (International Journal of Evaluation and Research in Education (IJERE), 2020)
This study was conducted in order to investigate the possible relationship between adherence to Islamic principles of success and academic performance of university students. Accordingly, a questionnaire based on Islamized principles of success (referred to as “Islamic character quotient inventory (ICQi)”) was correlated with CGPA (Cumulative Grade Point Averages) of 343 students of Usmanu Danfodiyo University, Sokoto. The empirical testing indicates that the total score on ICQi correlated positively and significantly with the academic performance of the respondent. Students with either high or medium adherence to ICQi have a significantly higher CGPA than their counterparts with the low-adherence level. However, the result did not show a significant relationship between the CGPA of highly adherent individuals and that of those with medium adherence level. The findings of this research may suggest that Islamic principles are not confined to the spiritual aspect of human’s life, but also relevant and useful for our mundane affairs.